Hyperglycaemic hyperosmolar state in an obese prepubertal girl with type 2 diabetes: case report and critical approach to diagnosis and therapy - Angelika Mohn; Nella Polidori; Valeria Castorani; Laura Comegna; Cosimo Giannini; Francesco Chiarelli; Annalisa Blasetti (BMC, 2021)
Abstract Introduction Isolated Hyperosmolar Hyperglycaemic Syndrome (HHS) is a life-threatening condition characterized by elevated serum glucose concentrations and hyperosmolality without significant ketosis. It is often described in obese adults with unknown Type 2 Diabetes (T2D), rarely in youth. In childhood the most common cause of metabolic glucose related derangement is Diabetic Ketoacidosis (DKA) in Type 1 Diabetes (T1D). Interestingly, both components can be combined with each other, thus the prevalent condition needs to be recognised implying a different therapeutic approach. Case presentation In this case, we report a prepubertal Caucasian obese girl admitted for two episodes of combined HHS/DKA in order to elucidate her clinical course taking into account the current pediatric recommendations based on adult guidelines for HHS. Conclusions The treatment of HHS and even more of HHS/DKA in youth is still controversial as no specific guidelines for children are available especially during the prepubertal age. The description of our case might be helpful and offer relevant points for future consensus.